Detection of the blood flow direction using heterodyne demodulation for a Doppler ultrasound system and its validation by simulation - García, F.; Solano, J.; Fuentes, M.; Rubio, E. (Revista Mexicana de Ingenieria Biomedica, 2015)
Doppler ultrasound blood flow measurement techniques have been widely used for the diagnosis of vascular diseases. In particular, some Doppler systems which may be able to determine the blood flow direction use signals produced by the homodyne quadrature demodulation technique. This approach has a major disadvantage since it has to process two channels (phase and quadrature), to equalize them (in amplitude) and to maintain these characteristics throughout the complete signal bandwidth. The work presented here, proposes an alternative method to determine the blood flow direction using heterodyne demodulation. The technique involves shifting the complete band of frequencies (where information of interest lies), at least a frequency equal to the bandwidth of the Doppler signal. This method simplifies the analog stage for the acquisition of the Doppler signal since it only needs to process one channel. Results of simulations show the effectiveness of the approach by determining the blood flow direction efficiently, in the frequency domain. It also reduces the generation of artifacts, in the band of interest, caused by differences in the phase and quadrature channels.